Legal Protection of Employee in Criminal Law in Poland (Art. 220 of the Polish Criminal Code) - Izydorczyk, Jacek (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The text presents the current status of protection provided for employee in the criminal code (Art. 220 of the Polish Criminal Code of 1997) and some verdicts of the Polish Supreme Court in this matter; the author concludes that Polish criminal law is so-called a “closed law” and any “wide interpretations” – including such against suspects or accused persons in criminal trials are clearly unacceptable; and whenever a problem arises in a criminal trial, whether or not we are dealing with a victim of a crime who is or was an “employee” – this specific human exposure to the immediate danger of loss of life or serious damage to his/her health should be qualified under Art. 160 of the Polish Penal Code – and not under Art. 220 of the Polish Penal Code.